Batman. Mystery of the Batwoman [videorecording (DVD)] - Reaves, Michael; Geda, Curt; Conroy, Kevin, 1955-; Dean, Margaret M.; Strong, Tara, 1973-; Zimbalist, Efrem, Jr., 1918-2014; Hastings, Bob, 1925-2014; Stiers, David Ogden; Elizondo, Hector; Ripa, Kelly, 1970-; Sedgwick, Kyra; Vernon, John, 1932-2005; et al. (Warner Home Video, 2003)
The Penguin and Rupert Thorn are criminal cohorts with a scheme to sell illegal weapons. Now, there's a new super hero in Gatham City who has other plans for the evil entrepreneurs - Batwoman! With high-tech gadgets and powerful punches, Batwoman proves a formidable crimefighter. When Batwoman crosses the criminal line, Batman must identify if she is an ally or foe.